#TITLE_ALTERNATIVE# - KUSTANDY (NIM: 13206003); Dosen pembimbing : Prof. Dr. Ir. Bambang Riyanto T., M.Sc., IRFAN
Active noise control (ANC) is a system that produce noise reduction technique with two sound waves destructive superposition method. This method is done by detecting noise signal, processing the signal to produce antinoise signal that has same amplitude but reverse in phase with the noise signal. ANC systems effectively reduce low frequency noise, while passive noise reduction techniques don‟t. Large dimension and high cost are the major constraint in passive noise reduction technique for low frequency noise. In this final project, ANC system is used to reduce a broadband knitting machine noise in open space. MIMO (Multi-Input-Multi-Output) FXLMS (Filtered-X Least Mean Square) algorithm is used to produce the antinoise signal, especially for multiple channel system implementation. This implementation uses four channel system of actuators and error sensors in order to obtain wider quiet zone effectively near the usual working place of machine operators. The experiments is done first by hardware testing with single channel ANC implementation for simple noise, ANC simulation for factory noise in laboratorium with single and multiple channel, and pratical implementation in factory with various geometries and configurations. Multiple channel ANC system is implemented on DSK TMS320C6713 with channel expansion using DSK_AUDIO16_BASE and two DSK_AUDIO4. Centralized and decentralized system is used for ANC system structure. The experiments is also done by using two reference sensors to handle diffused multiple-point noise sources. The maximum reduction obtained in experiments at laboratory is 1 dBA for single channel with geometry 1b and 0.85 dBA for multiple channel with geometry 2a. In pratical implementation in factory, maximum reduction is 0 dBA for single channel with geometry 1b and 0.5 dBA for multiple channel with geometry 2c.